ANALISIS KADAR GULA DALAM DARAH KARYAWAN UNISMA (Studi Kasus Pada Karyawan di Unisma Bekasi) - Zulkarnaen .; Dindin Abidin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2006)
Diabetes is not a new disease. Egyptians in 1552 BC have recognized it. The symptom occurs in high frequency of urinating, rapid loss of body weight, and pain. They named it Poliuria. In 400 BC, an Indian writer, Sushrutha, named it a honey urine disease. It was in 200 BC that this disease is called Diabetes Mellitus for the first time. Diabetes is a bully for many sufferers. Unfortunately, most of them do not realize it. Even the limit of blood sugar in more than 80% of the sufferers is not well-controlled. Based on the result of a test and measurement carried out to 63 Unisma workers, it can be concluded as this: the condition of blood sugar limit in their bodies is commonly well; it means that they are not diabetic. Instead, most of them have the amount of blood sugar below normal level. And it is as dangerous as having diabetes itself.